The Non-Aligned Movement and the NPT Review Process - E. B. Mikhaylenko; E. S. Poriadina (Vestnik MGIMO-Universiteta)
The Non-Aligned movement is one of the most active and large groups within the negotiation process for the Treaty on the Non-Proliferation of Nuclear Weapons. The NAM promoted radical disarmament agenda during the conferences on the NPT for the last decade. However, it proves to be inefficient. The article aims at uncovering the NAM priorities, as well as defining its role in agenda setting during NPT negotiation process. The authors show transition from simple declarations to specific plans and projects of the NAM in the nonproliferation sphere. Critical document analysis of the NAM states and informal interviews on the margins of the 2018-2019 non-proliferation committees provided the necessary information for the research. Internal challenges within the NAM were analyzed. The authors conclude that although the NAM has a lot of members with pro-active positions, their actions were unsuccessful due to internal conflicts and polar stances on the issue. This, in turn leads to clash of interests within the NAM and to a very broad agenda. The NAM is still weak to form a united front in order to contend nuclear powers’ position.